Sensory Evaluation of Flakes from Purple Sweet Potato Flour with the Addition of Edamame Flour Using the Just About Right (JAR) Method - Widianti, Erika; Sarofa, Ulya; Kurnianto, Muhammad Alfid (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Sensory evaluation is a crucial activity in food product development and affects consumer preference, particularly for flake products. Flakes are foods in the form of thin or flaky pieces, generally made from cereal grains. The raw materials used in this study are purple sweet potato flour, which is high in starch (74.57%), and edamame flour, which is high in protein (36.15%). Different formulations will affect the formation of sensory attributes and characteristics of flake products. The sensory evaluation method used in this study is the Just About Right (JAR) method, aimed at analyzing the sensory attributes of flake samples that influence overall liking assessment (p-value < 0.05; panelist response percentage > 20%; and high mean drops), in order to determine the most optimal product formulation. Sensory evaluation of the product was conducted by testing 13 attributes using JAR and hedonic scales (overall liking). The data obtained were processed using XLSTAT 2024 software. Based on the analysis results, the F2 flake product formulation (80% Purple Sweet Potato Flour: 20% Edamame Flour) is the most optimal product formulation, where the attributes that need optimization are taste (Earthy – Sweet, p-value = 0.027) and aftertaste (Earthy, p-value = 0.0003).